A quality by design approach for the development of lyophilized liposomes with simvastatin - Alina Porfire; Dana Maria Muntean; Lucia Rus; Bianca Sylvester; Ioan Tomuţă (Elsevier, 2017)
Lyophilization is used to ensure an increased shelf-life of liposomes, by preserving them in dry state, more stable than the aqueous dispersions. When stored as aqueous systems, the encapsulated drugs are released and the liposomes might aggregate or fuse. The aim of this study was to develop and optimize a lyophilized formulation of simvastatin (SIM) loaded into long circulating liposomes using the Quality by Design (QbD) approach. Pharmaceutical development by QbD aims to identify characteristics that are critical for the final product quality, and to establish how the critical process parameters can be varied to consistently produce a product with the desired characteristics. In the case of lyophilized liposomes, the choice of the optimum formulation and technological parameters has to be done, in order to protect the integrity of the liposomal membrane during lyophilization. Thus, the influence of several risk factors (3 formulation factors: PEG proportion, cholesterol concentration, the cryoprotectant to phospholipids molar ratio, and 2 process parameters: the number of extrusions through 100 nm polycarbonate membranes and the freezing conditions prior lyophilization) over the critical quality attributes (CQAs) of lyophilized long circulating liposomes with simvastatin (lyo-LCL-SIM), i.e. the size, the encapsulated SIM concentration, the encapsulated SIM retention, the Tm change and the residual moisture content, was investigated within the current study using the design of experiments tool of QbD. Moreover, the design space for lyo-LCL-SIM was determined, in which the established quality requirements of the product are met, provided that the risk factors vary within the established limits.